2022
DOI: 10.1027/1016-9040/a000473
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Creativity Framework

Abstract: Abstract. The dynamic creativity framework (DCF) represents a new theoretical perspective for studying the creativity construct. This framework is based on the dynamic definition of creativity, and it has both theoretical and empirical implications. From a theoretical point of view, we review the characteristics of the dynamic creative process and its extension into the dynamic universal creative process, encompassing creativity at different layers of complexity. We discuss the key concept of creative potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 88 publications
0
12
0
Order By: Relevance
“…While engaging in creative pursuits in any domain of human endeavor, these diverse operations of creative cognition are orchestrated together and reflect the underlying integrated dynamic. 2 , 31 , 32 , 36 , 43 , 53 , 54 This dynamic interplay between both brain hemispheres through specific nodes (network hubs) 33 , 35 , 37 , 38 , 55 remodels the mental workspace, the deliberate and spontaneous modes, and the flow of experience. 18 , 56 , 57 , 58 In the subsequent sections, we will emphasize these underpinning dynamics.…”
Section: Creative Mental Operationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While engaging in creative pursuits in any domain of human endeavor, these diverse operations of creative cognition are orchestrated together and reflect the underlying integrated dynamic. 2 , 31 , 32 , 36 , 43 , 53 , 54 This dynamic interplay between both brain hemispheres through specific nodes (network hubs) 33 , 35 , 37 , 38 , 55 remodels the mental workspace, the deliberate and spontaneous modes, and the flow of experience. 18 , 56 , 57 , 58 In the subsequent sections, we will emphasize these underpinning dynamics.…”
Section: Creative Mental Operationsmentioning
confidence: 99%
“…[28][29][30] Fast forward to the present day, and the latest trend in the physiological approach to understanding creativity is to characterize the mechanisms underlying creativity in the context of brain networks. 2,25,[31][32][33][34][35][36][37] The range of paradigms, tasks, and techniques that have been used in the physiological approach has led to a diverse constellation of findings, and these have been used in different ways to explain the basis of creativity from the perspective of the nervous system. 2,20,37,38,39 The physiological approach to creativity has explored the relationship of creative engagement to the activity of the peripheral nervous system, such as enhanced sympathetic cardiac activity during divergent thinking (DT) 40,41 and increased pupil dilation during music-induced aesthetic "chills".…”
mentioning
confidence: 99%
“…He concluded that if we want to have good ideas, we must have lots of ideas and learn to throw away the bad ones (as cited in Kirwan, 2017; see also Lortie, 2017). Although much knowledge exists on individuals’ creative potential on a between-person level as the potential to solve open problems (e.g., Barbot, 2018; Fink & Benedek, 2014; Runco & Acar, 2012), research has largely neglected the moment-to-moment fluctuations of creative ideation performance (i.e., the momentary realization of one’s creative potential; but see, e.g., Andrews-Hanna & Grilli, 2021; Barbot, 2019, 2022; Corazza et al, 2022; Guilford, 1950). The well-known serial order effect in idea generation, which describes an increase in the average originality of ideas with time on the task, constitutes one prominent exception of this strong between-person focus (Beaty & Silvia, 2012; Christensen et al, 1957).…”
Section: Benefits Of An Ecological Momentary Assessment (Ema)mentioning
confidence: 99%
“…Creativity is widely recognized as a crucial skill for future development, particularly in the era of artificial intelligence. It is a multifaceted process that involves the interconnectedness of dynamic episodes through concatenation, dynamic estimation, and exaptation mechanisms ( Corazza et al, 2022 ). Over the past decade, numerous studies utilizing functional magnetic resonance imaging (fMRI) have explored the neural processes underlying creative thinking ( Khalil et al, 2023 , Kleinmintz et al, 2019 , Madore et al, 2019 , Palmiero et al, 2022 , Ren et al, 2023 , Sunavsky and Poppenk, 2020 , Takeuchi et al, 2020 , Zhuang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most fMRI studies on creativity have utilized divergent thinking tasks that measure originality without considering valuableness. However, both originality and valuableness (or usefulness and effectiveness) are acknowledged as pivotal factors for creative performance ( Corazza et al, 2022 ; Ren et al, 2023 ; Yeh et al, 2019 ; Zhu et al, 2020 ). Creativity tasks emphasizing both indices involve a cyclical shift between the processes of idea generation and evaluation ( Lin and Vartanian, 2018 ); the brain activations may differ from those emphasized in tasks focusing solely on originality.…”
Section: Introductionmentioning
confidence: 99%